Balancing Digital and Physical Reading: An Empirical Study on Student Preferences, Challenges, and Adaptive Strategies - Rao, R. Raghavendra (Journal of Information and Knowledge, 2025)
Technology has changed the entire lifestyle of people and has become an integral part of regular activities. Modern technology has made a significant impact on our lives in such a way that we depend on using technical devices for work at home and office. It has hit every field of our life and education is not an exception. In fact, the education sector is the most affected one by the advent of technology in recent times. The COVID pandemic forced students to step into the digital world for their educational needs. Online learning has transformed the students’ reading habits and behaviour. The present study focuses on understanding the student preferences and perceptions towards digital and physical reading habits. The study was conducted in one of the state universities in Andhra Pradesh through questionnaire and personal interviews. The main purpose of the study is to understand the reasons for switching between digital and physical reading habits. Also, it explores the association between selected demographical variables and perceptions of students’ reading preferences. The research outcomes with the strategies can be adopted to improve reading behavior among young generation and a wellbalanced learning experience between physical and digital formats.